2016
DOI: 10.1126/science.aag0246
|View full text |Cite|
|
Sign up to set email alerts
|

Coordination-induced weakening of ammonia, water, and hydrazine X–H bonds in a molybdenum complex

Abstract: Although scores of transition metal complexes incorporating ammonia or water ligands have been characterized over the past century, little is known about how coordination influences the strength of the nitrogen-hydrogen and oxygen-hydrogen bonds. Here we report the synthesis of a molybdenum ammonia complex supported by terpyridine and phosphine ligands that lowers the nitrogen-hydrogen bond dissociation free energy from 99.5 (gas phase) to an experimentally measured value of 45.8 kilocalories per mole (agreein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
192
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(209 citation statements)
references
References 64 publications
11
192
0
Order By: Relevance
“…[5] In this regard,t reating 4-methoxys- [25] Similara ctivation of hydrazine, by weakening of NÀHb ond of hydrazine upon coordination of hydrazinew ith molybdenum-terpyridine-phosphine has also been demonstrated. [26] It has been observedt hat such metal hydrazinec omplexation lower the nitrogen-hydrogen bond dissociation free energy (34.6 kcal mol À1 )a nd hence enable H 2 evolution and hydrogenation of styrene. [26] Analogous Ru-hydride and Ru-diazene intermediates werea lso observed during dehydrogenation of hydrazine over Ru-tetradentate phosphine complexes via a" coordination induced activation pathway".…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] In this regard,t reating 4-methoxys- [25] Similara ctivation of hydrazine, by weakening of NÀHb ond of hydrazine upon coordination of hydrazinew ith molybdenum-terpyridine-phosphine has also been demonstrated. [26] It has been observedt hat such metal hydrazinec omplexation lower the nitrogen-hydrogen bond dissociation free energy (34.6 kcal mol À1 )a nd hence enable H 2 evolution and hydrogenation of styrene. [26] Analogous Ru-hydride and Ru-diazene intermediates werea lso observed during dehydrogenation of hydrazine over Ru-tetradentate phosphine complexes via a" coordination induced activation pathway".…”
Section: Resultsmentioning
confidence: 99%
“…[26] It has been observedt hat such metal hydrazinec omplexation lower the nitrogen-hydrogen bond dissociation free energy (34.6 kcal mol À1 )a nd hence enable H 2 evolution and hydrogenation of styrene. [26] Analogous Ru-hydride and Ru-diazene intermediates werea lso observed during dehydrogenation of hydrazine over Ru-tetradentate phosphine complexes via a" coordination induced activation pathway". [27] Based on the above findings and spectrald ata (mass and 1 HNMR) we proposed ap lausible general reaction pathway for the hydrazine activation with ruthenium complexes shown in the Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentionedi nt he introduction, there are several known mechanisms for water activation,i ncluding (1) oxidative addition to as inglet ransitionm etal center, [10a, 22] ab inuclear transition metal center, [10] or ag eometrically constrained main group element, [11] (2) OÀHc ooperative cleavage by at ransition metal and its supporting ligands, [12] and (3) coordination-induced weakening of OÀHb onds to form H 2(g) . [13] In the current system,w ef ound that OÀHb onds of water were cleaved through au nique ligand-ligand cooperation fashion.T his represents an ovel pathwayf or water activation.…”
mentioning
confidence: 99%
“…[12] Recently,i tw as also found that OÀHb ond can be weakened via water coordinationt oaMo complex, then activated with the evolution of H 2 . [13] H 2 Oi sw eakeneda nd activated by coordinationt oatitanium center or through the second coordination sphere interactioni n[ Cp 2 TiCl], [14] thus serving as ah ydrogen-atomt ransfer reagent. [15] In this work, we demonstrate that an isolated vanadium-bound thiyl radicals peciesh as the reactivity to activate H 2 Oa nd CH 3 OH through the cleavage of strong OÀHa nd CÀO bonds.…”
mentioning
confidence: 99%